Effects of Ordinary Portland Cement in Parit Haji Ali Peat Soil on Compression Strength - Marzuki, Muqri; Pakir, Faizal (Recent Trends in Civil Engineering and Built Environment, 2025)
Peat is categorised as a soft soil due to its high porosity, extreme compressibility, high squeezability, and low shear strength. In recent years, adding Ordinary Portland Cement (OPC) to improve its properties and enhance its strength has been establish in saveral places. However, the optimum amount of OPC required to stabilised every peat is different depend on its properties. Therefore, there is a need to investigate the effects of OPC on Parit Haji Hali peat and find the optimum value of OPC required to stabilize the peat. A few laboratory test were performed to investigate the fundamental characteristics of raw peat soil, including humification level, moisture content, organic content, liquid limit, specific gravity, fibre content, and pH. Then, the Unconfined Compresssive Strength test were perform on treated samples with two diffrent binder content (300 kg/m3 and 350 kg/m3) and different curing period (7,14 and 14 days) with a target of 50 kPa. The results showed the optimum cement dosage 300 and 3500 kg/m3 for Parit Haji Ali hemic peat was sufficient to achieve the target strength of 56.88 and 67.54 kPa at 7 days, respectively. The comparison of unconfined compressive strengths in treated peat with densities of 300 kg/m³ and 350 kg/m³ consistently demonstrates higher strength values associated with the increased binder density and curing period.